Introducing language and society - Jones, Rodney H. 1959-; Themistocleous, Christiana 1979- (Cambride introductions to language and linguistics, 2022)
This accessible and entertaining textbook introduces students to both traditional and more contemporary approaches to sociolinguistics in a real-world context, addressing current social problems that students are likely to care about, such as racism, inequality, political conflict, belonging, and issues around gender and sexuality. Each chapter includes exercises, case studies and ideas for small-scale research projects, encouraging students to think critically about the different theories and approaches to language and society, and to interrogate their own beliefs about language and communication. The book gives students a grounding in the traditional concepts and techniques upon which sociolinguistics is built, while also introducing new developments from the last decade, such as translanguaging, multimodality, superdiversity, linguistic landscapes and language and digital media. Students will also have online access to more detailed examples, links to video and audio files, and more challenging exercises to strengthen their skills and confidence as sociolinguists